Pendidikan Akhlak Sebagai Pembangun Fitrah Manusia Perspektif Ibnu Maskawih - Wiwi Dwi Daniyarti (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
At this time, human morality begins to experience degradation from many dimensions, moral degradation occurs not without cause, but because many things in the soul do not grow perfectly in their formation. There are stages that are passed unknowingly, especially with the times and increasingly advanced technology, making humans neglect to fulfill the good nature/potential that should grow with the times. If this continues, there will be many people who grow not according to their nature, problems related to this need to be studied more deeply. One of the figures closely related to this is Ibnu Miskawaih. According to Ibnu Miskawaih, the soul in humans must be well-filled which will give birth to nature or self-potential so that it encourages humans to do good deeds without thinking first. So this study aims to examine more deeply related to human nature which can be grown by moral education with the study material conducted by Ibnu Miskawaih as well as analyzing Ibn Miskawaih's thoughts regarding moral education. This study uses a qualitative approach with the method of literature study or literature study by collecting the necessary data sources. Moral education according to the concept of Ibn Miskawaih can be used as a building element of nature or basic potential possessed by humans so that humans have moral perfection and human perfection. Human perfection (insan kamil) is a human being who can balance the inner and outer aspects so as to give birth to humans who can create peace and prosperity in the perfection of life.